(untitled) (Journal of Engineering, 2011)
Treatment of a high strength acidic industrial wastewater was attempted by activated carbon adsorption to evaluate the feasibility of yielding effluents of reusable qualities. The experimental methods which were employed in this investigation included batch and column studies. The former was used to evaluate the rate and equilibrium of carbon adsorption, while the latter was used to determine treatment efficiencies and performance characteristics. Fixed bed and expanded bed adsorbers were constructed in the column studies. In this study, the adsorption behavior of acetic acid onto activated carbon was examined as a function of the concentration of the adsorbate, contact time and adsorbent dosage. The adsorption data was modeled with Freundlich and Langmuir adsorption isotherms.The amount of acetic acid adsorbed increased with the decrease in initial concentration of acetic acid and increased with the increase in contact time and adsorbent dose. The effects of various important and influencing parameters such as flow rate, bed height, inlet adsorbate concentration on breakthrough curve are studied in details in the column studies.